Almost the same but not quite: Mimicry e Subversão em Youth e Foe de J. M. Coetzee - Bispo, Jéssica (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
This article analyzes, through a postcolonial perspective, the literary works Foe and Youth, both written by J. M. Coetzee. It problematizes the concept of mimicry as presented by Homi K. Bhabha in his essay “Of mimicry and man: The ambivalence of colonial discourse”. Analyzing the actions of the characters John and Friday, it becomes possible to perceive how they resort to strategies of mimicry and attempt to resist Western discourses of power. Consequently, they present themselves as disruptive and subversive in a cultural space traditionally imbedded with colonial authority.